Foam Cell Macrophages in Tuberculosis - Agarwal, Pooja; Gordon, Siamon; Martinez, Fernando O. (Frontiers in Immunology, 2021)
Mycobacterium tuberculosis infects primarily macrophages in the lungs. Infected macrophages are surrounded by other immune cells in well organised structures called granulomata. As part of the response to TB, a type of macrophage loaded with lipid droplets arises which we call Foam cell macrophages. They are macrophages filled with lipid laden droplets, which are synthesised in response to increased uptake of extracellular lipids, metabolic changes and infection itself. They share the appearance with atherosclerosis foam cells, but their lipid contents and roles are different. In fact, lipid droplets are immune and metabolic organelles with emerging roles in Tuberculosis. Here we discuss lipid droplet and foam cell formation, evidence regarding the inflammatory and immune properties of foam cells in TB, and address gaps in our knowledge to guide further research.